Effectiveness of blood donor screening by HIV, HCV, HBV‐NAT assays, as well as HBsAg and anti‐HBc immunoassays in Germany (2008–2015). Issue 5 (22nd April 2019) - Fiedler, Sarah A.; Oberle, Doris; Chudy, Michael; Scheiblauer, Heinrich; Henseler, Olaf; Halbauer, Jochen; Heiden, Margarethe; Funk, Markus
Abstract : Background and Objectives: In Germany, in addition to standard blood donor screening, further mandatory tests were introduced for HCV‐RNA, HIV‐1‐RNA and for anti‐HBc. Screening for HBV‐DNA is optional. This study investigates the benefits of these additional tests for the detection of HIV, HCV, and HBV infections among German blood donors. Materials and Methods: From 2008 to 2015 we collected data on blood donations exclusively testing NAT positive (NAT yield) or reactive in only one of the screening assays. Assuming a Poisson distribution, we calculated NAT yield/reactive only rates on a per donation basis (number of yield/reactive only cases divided by the number of donations tested in the period under review) with 95% confidence intervals. Results: Responding establishments covered 95% of the donations. We identified 20 HIV‐1‐NAT, 61 HCV‐NAT and 29 HBV‐NAT yield cases among approximately 46 million blood donations tested corresponding to 0·43 HIV‐1 NAT, 1·32 HCV‐NAT, and 0·64 HBV‐NAT yield cases per million blood donations tested. For one HBsAg reactive only case and 23 anti‐HBc reactive only cases in repeat donors, infection was confirmed by ID‐NAT which translates into 0·02 and 0·55 cases per million donations tested. During the 8‐year‐observation period, one HIV‐1, no HCV and four HBV transmissions associated with donations in the viremic pre‐seroconversion window period were reported. Conclusion: Annually, NAT screening alone detected 2·5 HIV‐1, 7·6 HCV, and 3·6 HBV infectious donations; anti‐HBc screening alone identified 2·9 infectious donations of repeat donors with occult HBV infection. Overall, the survey results support that the currently practiced donor HIV/HCV/HBV screening strategy in Germany does ensure a high standard of blood safety.